All Days 2003
DOI: 10.2118/81021-ms
|View full text |Cite
|
Sign up to set email alerts
|

Three-Phase Relative Permeability of Petroleum Reservoirs

Abstract: This paper presents a critical review of recent experimental and theoretical developments in the area of three-phase relative permeability along with a comparative evaluation of several models for estimating the oil relative permeability under three-phase flow conditions. Reported experimental data on three-phase relative permeability were screened for reliability and completeness and three representative data sets were selected for use in evaluation of the prediction techniques. Eight differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…It is a homogeneous reservoir and replicates the high-permeability, intermediate-wet sample (Sample 15) of Oak (1991). Eight components were used to represent light oil with the Peng-Robinson equation of state (Peng and Robinson 1976). The simulation model has two wells, an injector and a producer, which are at the opposite ends of the reservoir model.…”
Section: Numerical-simulation Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a homogeneous reservoir and replicates the high-permeability, intermediate-wet sample (Sample 15) of Oak (1991). Eight components were used to represent light oil with the Peng-Robinson equation of state (Peng and Robinson 1976). The simulation model has two wells, an injector and a producer, which are at the opposite ends of the reservoir model.…”
Section: Numerical-simulation Results and Discussionmentioning
confidence: 99%
“…It implies that the saturation-averaged interpolation method is a common choice in more-recent models in place of other mathematical models, such as capillary models, statistical models, and network models. Several investigators (Fayers and Matthews 1984;Delshad and Pope 1989;Baker 1988;Oak 1990Oak , 1991Hustad and Holt 1992;Skjaeveland and Kleppe 1992;Balbinski et al 1999;Pejic and Maini 2003;Spiteri et al 2008;Ahmadloo et al 2009) have identified various limitations of classical three-phase relative permeability models such as Stone I (Stone 1970) and Stone II (Stone 1973), especially for nonwater-wet rocks and/or at low oil saturation. Although the majority of three-phase relative permeability models found in Table 1 are applicable only to water-wet conditions, many oil reservoirs are not strongly water-wet and their wettability may be altered in various ways (Treiber and Owens 1972;Morrow 1990).…”
Section: Three-phase Relative Permeability Modelsmentioning
confidence: 99%
“…The Stone I model suggests that, in a water-wet medium, relative permeabilities of gas and water (non-wetting and wetting phases) are the same as their two-phase counterparts as observed in gas-oil and oil-water displacements, respectively. Relative permeability of the intermediate wetting phase, oil in this case, depends on the phaseconfiguration within the pore space, which in turn depends on both water and gas saturations (Pejic and Maini, 2003). The modified Stone I model is defined by the following set of equations.…”
Section: Three-phase Relative Permeabilitymentioning
confidence: 99%
“…Relative permeability of the intermediate wetting phase, oil, depends on the phase configuration within the pore space, which in turn depends on both water and gas saturations (Pejic and Maini, 2003 where is the three-phase residual oil saturation, and is the maximum oil relative permeability in a two-phase oilwater displacement process.…”
Section: Three-phase Relative Permeabilitymentioning
confidence: 99%